Bibliometric Analysis Toxicity Levels of MOBA Game Players Among Students and the General Public - Neng Cahya Ningsih; Gary Gibran Amnesty (Westscience Press, 2024)
Multiplayer Online Battle Arena (MOBA) games have become a global phenomenon in the gaming industry. This article aims to examine the evolution, impact, and social aspects of MOBA games. We analyzed various literature sources, including scientific journals, articles, and research reports relevant to the keyword